Copper and zinc accumulation and fractionation in a clayey Hapludox soil subject to long-term pig slurry application - Formentini, Thiago Augusto; Mallmann, Fábio Joel Kochem; Pinheiro, Adilson; Fernandes, Cristovão Vicente Scapulatempo; Bender, Marcos Antonio; da Veiga, Milton; dos Santos, Danilo Rheinheimer; Doelsch, Emmanuel (The Science of the total environment, 2015)
Pig slurry (PS) recycling as fertilizer is commonly practiced as an option for minimizing livestock waste. Successive PS applications on the soil can lead to crop toxicity and environmental risk. Despite extensive investigation of macronutrient behavior, the fate of trace metals remains uncertain and only a few long-term field studies have been reported to date. This study was designed to assess the impact of 11-year continuous PS spreading on Cu and Zn accumulation and fractionation in a Brazilian clayey Hapludox soil. Three different PS application rates – 50, 100 and 200m3ha−1year−1 – were monitored at six soil depths in comparison to a non-amended control soil. The modified Geological Survey of Canada sequential extraction protocol was applied. A statistically significant increase in Cu and Zn total concentration (assessed by the sum of fractions) was noted only within the 0–5cm soil layer for the 50 and 100m3ha−1year−1 (PS50 and PS100) treatments, and up to 10–15cm for the 200m3ha−1year−1 (PS200) treatment. The mass balance, determined for the 22 PS amendments over the period, confirmed the overall exogenous Cu and Zn accumulation within the surface layers. More than 70% of the natural heavy metal content was originally in the residual fraction. However, this was the only fraction not influenced by the PS amendments. After PS input, the exogenous Cu was mainly detected in the fraction bound to organic matter (66.4%) within the PS200 0–5cm soil layer. Exogenous Zn was mainly distributed between the adsorbed fraction (36.7%) and the organic matter fraction (32.0%) within the PS200 0–5cm layer. •We assessed the impact of 11-year pig slurry spreading at three different rates.•Heavy metals (HM) accumulated within the upper soil layers.•Exogenous Cu was mainly detected in the organic matter (OM) fraction.•Exogenous Zn was distributed between the OM and the adsorbed fractions.